Molecular Characterization of Methicillin Resistant and Extended Spectrum ?-Lactamase Staphylococcus aureus Isolated from Burn Patients - Ahmed Aziz, Shawnm (Kurdistan Journal of Applied Research, 2020)
Antibiotic resistance has become a major world health challenge and has limited the ability of physician's treatment. Staphylococcus aureus the most notorious pathogens causes morbidity and mortality especially in burn patients. However, Staphylococcus aureus rapidly acquired resistance to multiple antibiotics. Vancomycin, a glycopeptide antibiotic remains a drug of choice for treatment of severe Methicillin Resistance S. aureus infections. This study aimed to detect the emergence of beta-lactam and glycopeptide resistance genes. 50 clinical specimens of S. aureus collected from burn patients in burn and plastic surgery units in Sulaimani-Iraq city. All specimens were confirmed to be positive for S. aureus. All the isolates were assessed for their susceptibility to different antibiotics depending on NCCL standards, followed by Extended Spectrum Beta Lactamase detection by double disk diffusion synergy test. The production of ?- lactamases was evaluated in the isolated strains by several routine methods and polymerase chain reaction. Among the isolates 94% were Methicillin resistance and 34.28% were Extended Spectrum Beta Lactamase producer. PCR based molecular technique was done for the bla genes related to ?- lactamase enzymes by the specific primers, as well as genes which related to reduced sensitivity to Vancomycin were detected. The results indicated that all isolated showed the PBP1, PBP2, PBP3, PBP4, trfA and trfB, graSR, vraS except the vraR gene and the prolonged therapy of Methicillin resistance infection with teicoplanin have been associated with progress of resistance and the rise of tecoplanin resistance may be a prologue to evolving Vancomycin resistance. In conclusion, beta-lactam over taking can rise Vancomycin- Intermediate S. aureus strains leading to appearance of Vancomycin resistance although the treatment of Vancomycin resistant infections is challenging.